Children are Losing Lives in the Name of Culture: The Health Impacts of Initiation Schools in South Africa - Chuene, Tiisetso Aubrey (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Background: On an annual basis, young boys lose their lives due to circumcisions performed at initiation schools across South Africa. Some of the initiates lose their manhood as a result of amputations and all these acts are done in the name of culture. Over the last few years, there have been more media reports in South Africa about improper traditional circumcisions coupled with poor health outcomes causing deaths of children admitted at initiation schools. Aims: This article explores the health impacts of traditional initiation schools in South Africa. Methods: This review followed desktop approach through utilization of secondary data. Systematic quantitative review technique was used to collect data. To get a better understanding of the context under investigation, desktop analysis was employed using the five steps of the data analysis process. Results: The themes identified in this study include challenges associated with the practice in relation to children's rights, ethical conflicts between traditional initiation practices and public health, commercialization of initiation schools, and complications associated with circumcision at initiation schools. Conclusion: There is insufficient enforcement of the laws and a lack of public knowledge regarding the impact of initiation on children. Even though South Africa's national and local governments have made significant attempts to control the initiation practices and uphold children's rights, significant law enforcement is still required to shield children from unsafe cultural customs. In addition to the ineffective execution of existing rules and regulations, the traditional initiation sector is burdened by a lack of direct, continuous, and efficient supervision of the operations of initiation schools. Received: 7 February 2024, Reviewed: 11 March 2024, Revised: 29 March 2024, Accepted: 16 April 2024.